Effect of continuity on reduction factors of bending moments and shear forces in grid slabs. (September 2017) - Alraie, Ali; Barik, Manoranjan
Abstract: Grid slab is a type of floor system consisting of beams running in both directions monolithic with the slab. It is usually employed for architectural reasons in large halls such as auditoriums, restaurants, theatres and other halls where column-free space is often the main requirement. The literature is silent on dealing with such type of slabs. Some international codes like the Syrian code focus on this type of slab and provide a table of reduction factors, but which is for simply supported slab only. These values are no longer valid for the case where continuity exists. Hence this paper attempts to study the effect of continuity on the reduction factors of bending moments and shear forces of grid beams in grid-slab and obtain the reduction factors for different cases of continuity. For validation of the results, SAP 2000 software is used to obtain those values for different cases of continuous slabs. For this, a number of models having different sizes of slabs are considered. A number of analyses are performed taking all probable cases into account for three different percentages of continuity: one-third, two-third and full-length. The investigation of the effect of continuity is carried out by considering a slab having five beams and the reduction factors of bending moments and shear forces are presented in tabular forms. The study shows that it is beneficial when continuity is taken into account ultimately resulting in an economical design. Abstract : Highlights: Reduction factors for bending moments of grid slabs are presented. Reduction factors for shear forces of grid slabs are presented. The codes provide reduction factors for only simply supported slabs. No available literature for the reduction factors of continuous slabs. Effect of continuity on reduction factors of slabs are presented for the first time.